Reverting to a Healthy Diet during Lactation Normalizes Maternal Milk Lipid Content of Diet‐Induced Obese Rats and Prevents Early Alterations in the Plasma Lipidome of the Offspring. Issue 17 (13th July 2022) - Castillo, Pedro; Kuda, Ondrej; Kopecky, Jan; Pomar, Catalina Amadora; Palou, Andreu; Palou, Mariona; Picó, Catalina
Abstract : Scope: This study aims to assess in rats whether normalizing maternal diet during lactation prevents the harmful effects of western diet (WD) consumption during the whole perinatal period on the lipidomic profile in maternal milk and offspring plasma. Methods and Results: Control dams (CON‐dams), fed with standard diet (SD); WD‐dams, fed with WD prior and during gestation and lactation; and reversion dams (REV‐dams), fed as WD‐dams but moved to SD during lactation are followed. Lipidomic analysis is performed in milk and plasma samples from pups. Milk of WD‐dams presents a different triacylglycerol composition and free fatty acid (FA) profile compared to CON‐dams, including an increased ratio of pro‐inflammatory to anti‐inflammatory long‐chain polyunsaturated FA. Such alterations, which are also present in the plasma of their offspring, are widely reversed in the milk of REV‐dams and the plasma of their pups. This is related with the recovery of control adiponectin expression levels in the mammary gland, and the presence of decreased expression of pro‐inflammatory factors. Conclusion: Implementing a healthy diet during lactation prevents early alterations in the plasma lipidome of pups associated to the maternal intake of an obesogenic diet, which may be related to the normalization of milk lipid content and the inflammatory state in the mammary gland. Abstract : Implementing a healthy diet during lactation prevents harmful effects of the maternal intake of an obesogenic diet during the whole perinatal period on the lipidomic profile in maternal milk and offspring plasma. The reversion of such alterations, which include different triacylglycerol and free fatty acid (FA) profiles, and an increased ratio of pro‐inflammatory to anti‐inflammatory long‐chain polyunsaturated FA, may be related to the normalization of the inflammatory state in the mammary gland.